Menggali Dimensi Poetik Agama: Sumbangan Kreatif Heidegger terhadap Agama - Kristiatmo, Thomas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
Religion continues to exist despite the various attacks directed to its various elements. The secularisation thesis does not apply to the contemporary world, wherein religion proves itself to be an institution that always finds a place through the endless changes in human civilisation that has witnessed a growing number of violence in the name of particular religious values. Heidegger’s ideas could serve as tools to unravel this pandemonium. His philosophy makes head or tail of the religion’s features that have gone awry due to the lack of mystical elements. Heidegger proposes a fresh way of understanding religion through his reflection on the significance of dwelling poetically. Drawing inspiration from Hölderlin, he reflects upon the importance of poiesis, that is, an understanding on how human beings should live out religion so that it could always be relevant and enlightening.